Analisis Pengaruh Tingkat Inflasi, Tingkat Suku Bunga Terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Jakarta Periode Tahun 2018 - Muhammad Tody Arsyianto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
Composite Stock Price Index (CSPI) is a reflection of the Indonesian economy, while JCI showed significant improvement of the Indonesian economy is in a state that is conducive and vice versa. To be able to know anything that can help JCI to consider several factors such as SBI interest rate, inflation. The purpose of this study was to determine the effect of SBI rates, inflation against JCI. The research was conducted on the Stock Exchange by using a sample of 12 (2018) consists of monthly data across variables during 2018 with the selection of the sample through a non probabability method is the method of purposive sampling samplingdan Data were analyzed by multiple linear regression analysis technique. Berdasarkanhasil analysis found SBI interest rates, inflation, affect the JCI. SBI interest rates, inflation partially significant negative effect on the JCI, this means an increase in SBI rates inflation can lead to impairment of JCI.